2018
DOI: 10.3389/fmed.2018.00242
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Kidney Disease: 10 Tips for Clinicians

Abstract: Increased longevity in people with cystic fibrosis (CF) means that more people are surviving long enough to develop kidney complications. Nephrologists and their colleagues now face a steep learning curve as many of them encounter patients with CF related kidney disease (CFKD) for the first time. This article presents perspectives from a medical sociologist with CF on what renal health professionals should know about people with CFKD. It outlines challenges that people with CFKD as they age, framing these stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The above-mentioned causes can significantly accelerate the disease-related decline in the glomerular filtration rate. Additionally, treating lung disease in CF may result in toxicity and drug-drug interaction complications, especially with aminoglycosides [25,26]. Renal pathologies in CF patients have been considered rare, but recently, renal problems such as diabetic glomerulopathy, amyloidosis, postinfectious glomerulonephritis, membranous nephropathy, chronic interstitial nephropathy or tubular damage have been observed more and more often [27].…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned causes can significantly accelerate the disease-related decline in the glomerular filtration rate. Additionally, treating lung disease in CF may result in toxicity and drug-drug interaction complications, especially with aminoglycosides [25,26]. Renal pathologies in CF patients have been considered rare, but recently, renal problems such as diabetic glomerulopathy, amyloidosis, postinfectious glomerulonephritis, membranous nephropathy, chronic interstitial nephropathy or tubular damage have been observed more and more often [27].…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence is presumably due to the onset of CFKD rather late in life. Along with improving treatments and increased longevity, however, the prevalence of kidney complications has been on the rise, and about 20% of pwCF over the age of 55 years have CFKD (Lai et al, 2019; Nazareth & Walshaw, 2013; Nowakowski, 2018; Schechter & Stecenko, 2011).…”
Section: Models Of Other Organs and Tissues Affected Later In Lifementioning
confidence: 99%
“…The spectrum of renal diseases in adult patients with CF has proven to be heterogeneous (Yahiaoui et al, 2009). Symptoms of CFKD include pain in the lower back, fluid retention in the lower body, electrolyte imbalance, asymptomatic nephrocalcinosis, hypercalciuria, nephritis, renal stones, and bacterial infections (Nowakowski, 2018;Yahiaoui et al, 2009). To ameliorate the disease, and possibly avoid transplantation, it is necessary that the disease is diagnosed in a timely manner.…”
Section: Kidneysmentioning
confidence: 99%
“…The deterioration of fibrosis can lead to the destruction of organ structure and functional decline or even failure, which significantly threatens human health ( 58 ). Kidney fibrosis is the main pathological feature of chronic kidney failure and manifests as tissue structure disorganisation ( 59 , 60 ). Piñeiro-Hermida et al ( 61 ) revealed an association between the development of idiopathic pulmonary fibrosis and telomere dysfunction and telomerase mutations.…”
Section: Kidney Fibrosismentioning
confidence: 99%